Neuropathic Pain Causes Pyramidal Neuronal Hyperactivity in the Anterior Cingulate Cortex - Zhao, Ruohe; Zhou, Hang; Huang, Lianyan; Xie, Zhongcong; Wang, Jing; Gan, Wen-Biao; Yang, Guang (Frontiers in Cellular Neuroscience, 2018)
The anterior cingulate cortex (ACC) is thought to be important for acute pain perception as well as the development of chronic pain after peripheral nerve injury. Nevertheless, how ACC neurons respond to sensory stimulation under chronic pain states is not well understood. Here, we used an in vivo two-photon imaging technique to monitor the activity of individual neurons in the ACC of awake, head restrained mice. Calcium imaging in the dorsal ACC revealed robust somatic activity in layer 5 (L5) pyramidal neurons in response to peripheral noxious stimuli, and the degree of evoked activity was correlated with the intensity of noxious stimulation. Furthermore, the activation of ACC neurons occurred bilaterally upon noxious stimulation to either contralateral or ipsilateral hind paws. Notably, with nerve injury-induced neuropathic pain in one limb, L5 pyramidal neurons in both sides of the ACC showed enhanced activity in the absence or presence of pain stimuli. These results reveal hyperactivity of L5 pyramidal neurons in the bilateral ACC during the development of neuropathic pain.